IMPROVING ANALYSIS OF FINANCIAL DISTRESS USING THE SPRINGATE SCORE METHOD AT PT PERTAMINA PATRA NIAGA PERIOD 2019–2023 - Salmi Qauly K. Pakaya; Sahmin Noholo; Muliyani Mahmud (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the financial distress condition of PT Pertamina Patra Niaga during 2019–2023 using the Springate Score (S-Score) model. Financial distress is a critical stage preceding potential bankruptcy, commonly detected through declining liquidity, profitability, and operational capability. This study employed a quantitative descriptive approach using secondary data sourced from audited financial statements. The Springate model, consisting of four key ratios (working capital to total assets, EBIT to total assets, EBT to current liabilities, and sales to total assets), was applied to evaluate the company’s financial stability. The results show fluctuating financial performance. PT Pertamina Patra Niaga was categorized as financially healthy (safe zone) in 2019, 2020, 2021, and 2023, but experienced financial distress in 2022 due to severe liquidity pressure and increased short-term liabilities. The overall average S-Score of 0.9453 places the company in the grey area, indicating potential vulnerability to financial instability. The findings highlight the importance of improving liquidity management, strengthening working capital, and increasing operational efficiency to prevent future distress. Distress dengan Metode Springate Score pada PT Pertamina Patra Niaga Periode 2019–2023